MEGALOBLASTIC CRISIS IN SICKLE CELL DISEASE–A RARE PHENOMENA WITH AVAILABLE REVIEW OF LITERATURE - DASH, MONICA; KUMARI, PRIYA; MOHINDRU, DIVYA; MISHRA, PRAGNYA P. (International Journal of Current Pharmaceutical Research, 2024)
Sickle cell disease (SCD) is an inherited disease where some red blood cells are shaped like sickles or crescent moons. This condition affects the blood and various organs of the body. These sickle cells also become rigid and sticky, which can slow or block blood flow, resulting in episodes of sickness that produce pain and other crisis. There are different types of crisis. SCD with a megaloblastic crisis is rare. The frequency of the carrier state determines the prevalence of sickle cell anemia. Here we describe a 20 y old female patient with sickle cell disease who experienced a megaloblastic crisis.